1999
DOI: 10.1530/eje.0.1410055
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a soluble inhibitor of thyroid iodination in primary cultures of thyroid cells

Abstract: Monolayer cultures of thyroid cells lose their iodide organification capacity a few days before the disappearance of thyroid peroxidase (TPO) activity. The present studies were performed in order to clarify this point. The above mentioned difference was due to the presence of an inhibitor in the monolayer thyroid cells culture, given that total homogenate prepared from confluent cells caused a significant inhibition of activity of TPO from fresh tissue. The inhibitor was localized in the 105 000 g supernatant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, the inhibitor is active on TPO isolated from fresh tissue and inhibits the iodide organification when it is added to free follicles. This inhibitor is thermostable, dialyzable, has a molecular mass of less than 2 kDa and it has no species specificity, as was shown in our previous work [1].…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…However, the inhibitor is active on TPO isolated from fresh tissue and inhibits the iodide organification when it is added to free follicles. This inhibitor is thermostable, dialyzable, has a molecular mass of less than 2 kDa and it has no species specificity, as was shown in our previous work [1].…”
mentioning
confidence: 72%
“…Our previous studies [1] demonstrated that monolayer primary cultures of bovine thyroid cells, maintained in the presence of insulin, produced a cytosolic inhibitor of TPO activity. Its molecular mass of less than 2 kDa coincides with that reported previously for the insulin mediators [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations